PRAKTIK POLIGAMI DI INDONESIA DALAM PERSPEKTIF M. QURAISH SHIHAB, HUSSEIN MUHAMMAD, DAN NASARUDDIN UMAR (THE PRACTICE OF POLYGAMY IN INDONESIA WITHIN THE PERSPECTIVES OF M. QURAISH SHIHAB, HUSSEIN MUHAMMAD, AND NASARUDDIN UMAR) - Nur Afni Khafsoh; Rukmaniyah Rukmaniyah; Karina Rahmi Siti Farhani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This article intends to discuss the thoughts of M. Quraish Shihab, Hussein Muhammad, and Nasaruddin Umar in interpreting polygamy in Islam. The practice of polygamy in Indonesian society has always been a controversial debate for the public. Even the media also brought the issue through films and video documentaries about the practices of polygamy in Indonesia. This phenomenon can indirectly affect the perspective and thinking of the community regarding the legitimacy of polygamy in the socio-cultural context of Indonesian society. Therefore, it is very important to examine the thoughts of the three Indonesian Islamic figures above as a mirror to see how the Indonesian Muslim community should interpret polygamy. This article was compiled based on qualitative research through library research and searching virtual data on the internet. The results showed that the perspectives of the three Islamic figures were very relevant and contextual to be applied in analyzing the phenomenon of polygamy in Indonesia. However, the meaning of polygamy within the society is still tend to be literal. Therefore, a more comprehensive perspective is needed and more attention to local aspects is also required so that polygamy can be placed fairly within society.Artikel ini bermaksud untuk membedah pemikiran M. Quraish Shihab, Hussein Muhammad, dan Nasaruddin Umar dalam memaknai poligami dalam Islam. Praktik poligami di masyarakat Indonesia selalu menjadi isu yang hangat dibicarakan oleh publik. Bahkan media turut membawa isu tersebut melalui film dan video dokumenter tentang praktik-praktik poligami di Indonesia. Fenomena ini secara tidak langsung dapat mempengaruhi cara pandang dan berpikir pada masyarakat berkenaan dengan keabsahan poligami dalam konteks sosial budaya masyarakat Indonesia. Oleh karena itu, sangat penting untuk mengkaji pemikiran tiga (3) tokoh Islam Indonesia di atas sebagai cermin untuk melihat bagaimana seharusnya masyarakat Muslim Indonesia memaknai poligami. Artikel ini disusun berdasarkan penelitian kuatitatif melalui studi pustaka dan penelusuran data-data virtual di internet. Hasil penelitian menunjukkan bahwa perspektif ketiga tokoh Islam tersebut sangat relevan dan kontekstual untuk diterapkan dalam membaca fenomena poligami di Indonesia. Mengingat selama ini pemaknaan masyarakat terhadap poligami masih literal, dan diperlukan perspektif yang lebih komprehensif dan memperhatikan aspek kelokalan agar poligami dapat didudukkan secara adil di masyarakat.